A general method for the creation of dilational surfaces - Freek G. J. Broeren (Nature Portfolio, 2019)
Methods for dilation are currently limited to specific shapes and curvatures, with the potential for some of the structure's shape to encroach onto the final dilated volume. Here, the authors develop a method for creating dilational structures from arbitrary surfaces that avoids volume encroachment.